The Effectiveness of the HELP Youth Mental Health Modul in Preventing Bullying - Pangaribuan, Helena; Rahman, Nurdin; Setyawati, Tri (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Bullying is a social phenomenon that cannot be avoided today. The Indonesian Child Protection Commission (KPAI) recorded that there were 253 cases of bullying from 2011 to 2016, 36 cases occurred, which if presented, 22.4% of the 161 cases occurred at school. School is no longer a comfortable place to gain knowledge and develop character, if it is not handled well there is a risk of mental disorders, depression and suicide.The aim of this research is to determine the effectiveness of the HELP adolescent mental health module in preventing bullying in students at SMAN 3 Palu. This research design is Research and Development with a quantitative approach to a quasi experimental, employing a two-group pretest-posttest design with a control group, involving a total of 90 respondents (45 in the intervention group and 45 in the control group). The instrument used was a questionnaire to collect data. Data analysis used univariate analysis, independent T tests, dependent T tests, chi-square tests, and multivariate analysis. All data was analyzed using SPSS. The HELP adolescent mental health module consists of 3 interconnected circles, namely: the innermost circle is teenagers as the focus of intervention, the next circle is teachers and parents whose aim is to provide support and monitoring in preventing bullying. Prevention of adolescent bullying increased after the model intervention, namely increasing from the moderate bullying category to mild bullying by 29.4%. Research in implementing the HELP adolescent mental health module can prevent bullying in adolescents. In further research, it is necessary to innovate methods by adding the use of applications for access to monitoring and evaluation by teenagers and teachers using easily accessible TikTok media in explaining educational material so that it can increase the effectiveness of the module.